Simple and Efficient Preconditioner for Surface Integral Solution of Scattering from Multilayer Dielectric Bodies - B. B. Kong; X. Q. Sheng (International Journal of Antennas and Propagation)
The computation of scattering from multilayer dielectric bodies is studied by using the combined tangential formulation (CTF) of surface integral solution. A simple and efficient preconditioner is designed for the surface integral solution of multilayer dielectric bodies and validated by numerical experiments. Compared with the traditional near field preconditioner, the proposed preconditioner significantly reduce CPU time and memory requirement. Furthermore, the multilevel fast multipole algorithm (MLFMA) is employed to improve the capability of the solutions. The trick of efficiently implementing MLFMA is presented for multilayer dielectric bodies. Numerical examples are presented to verify the accuracy and efficiency of the approach for computing scattering from multilayer dielectric problems.